Analysis of Optimizing MSME Profits Through Financial Management Competence in Tarakan City - Islami, Rahmi Nur; Usman, Ferawati; Utomo, Mohammad Nur (Jurnal Ilmiah Ekonomi Islam, 2024)
Purpose his research aims to measure the extent of financial management competence possessed by MSME players, including Education and Training, Legal Compliance, Partnerships, and Networks, as well as the Application of Digital Technology in optimizing their profits. Methodology The research method used by researchers is quantitative. This research was conducted on 100 MSMEs in Tarakan City. Data collection was carried out using a structured questionnaire. The sampling technique used in this research was simple random sampling. The data analysis technique uses multiple linear regression analysis using the SmartPLS program. Findings The analysis results show that education and training have a significant positive impact on optimizing MSME profits. Apart from that, Legal Compliance also has a significant positive impact on optimizing MSME profits. Networking has a significant positive impact on optimizing MSME profits. Digitalization positively optimizes MSME profits, although the impact may not be as strong as other variables. Originality The development of MSMEs in Tarakan City was followed by various problems, including not yet optimal financial management, which resulted in the difficulty of achieving optimal profit. Financial management is a problem in MSMEs because MSME owners often ignore the importance of recording financial reports. Thus, financial management is essential to apply to MSMEs.